2014
DOI: 10.1371/journal.pone.0107619
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in Multiple Task Monitoring

Abstract: Coordinating multiple tasks with narrow deadlines is particularly challenging for older adults because of age related decline in cognitive control functions. We tested the hypothesis that multiple task performance reflects age- and gender-related differences in executive functioning and spatial ability. Young and older adults completed a multitasking session with four monitoring tasks as well as separate tasks measuring executive functioning and spatial ability. For both age groups, men exceeded women in multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 57 publications
2
23
0
Order By: Relevance
“…Counter accuracy correlated significantly with MRT, providing additional support for the hypothesis that multitasking performance is related to individual differences in spatial ability. The correlation data also showed that letter memory scores were positively related to multitasking performance but not to MRT, possibly due to the verbal nature of the updating task (cf., Salway & Logie, 1995;Todorov et al, 2014). A regression analysis showed that both MRT (Beta = .26, p < .01) and letter memory (Beta = .24, p < .01), were significant predictors of counter accuracy.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Counter accuracy correlated significantly with MRT, providing additional support for the hypothesis that multitasking performance is related to individual differences in spatial ability. The correlation data also showed that letter memory scores were positively related to multitasking performance but not to MRT, possibly due to the verbal nature of the updating task (cf., Salway & Logie, 1995;Todorov et al, 2014). A regression analysis showed that both MRT (Beta = .26, p < .01) and letter memory (Beta = .24, p < .01), were significant predictors of counter accuracy.…”
Section: Resultsmentioning
confidence: 91%
“…Sample size was determined on the basis of our previous studies with similar tasks (Mäntylä, 2013;Todorov et al, 2014). A large majority of the participants were University of Trieste undergraduates, and the remaining participants were young adults with a similar level of education and socio-economic status as the student sample.…”
Section: Study 1 Methodsmentioning
confidence: 99%
See 3 more Smart Citations